ANALISIS PEMBIAYAAN BERMASALAH DI UPK KECAMATAN SEJANGKUNG PENGELOLAAN DANA AMANAH PEMBERDAYAAN MASYARAKAT SIMPAN PINJAM UNTUK KELOMPOK PEREMPUAN - mulyanto mulyanto (Sebi : Studi Ekonomi dan Bisnis Islam, 2023)
The Ex-PNPM Community Empowerment Trust Fund is a revolving fund from the government managed by the Inter-Village Cooperation Agency through the Activity Management Unit in the Savings and Loans Program for women's groups. The number of problematic financing experienced by the UPK makes researchers interested in examining the problems that exist in the UPK, Sejangkung District, Sambas Regency. The purpose of this study is to find out what causes the amount of problematic financing at the Sejangkung District UPK and provide solutions to resolve these problems. The method used in this study is a descriptive qualitative method. Data collection techniques used are interview, documentation and direct observation. The results of this study can be concluded that the non-performing financing is due to the large number of members who are stuck in their business, the collateral that is pledged does not match the loan and the group administrators abuse their authority when managing the group.